2021
DOI: 10.1111/sdi.13009
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring in an end‐stage renal disease patient with diabetes receiving hemodialysis

Abstract: Diabetes is the leading cause of end‐stage renal disease (ESRD) and contributes to heightened morbidity and mortality in dialysis patients. Given that ESRD patients are susceptible to hypoglycemia and hyperglycemia via multiple pathways, adequate glycemic monitoring and control is a cornerstone in diabetic kidney disease management. In ESRD, existing glycemic metrics such as glycated hemoglobin, self‐monitored blood glucose, fructosamine, and glycated albumin have limitations in accuracy, convenience, and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…In non-CKD patients, clinical trials have shown that CGM is superior to SMBG in hypoglycemia detection and improved clinical outcomes. Several studies support the agreement of blood versus CGM-based interstitial glucose levels in advanced CKD patients [74–76], and anecdotal reports suggest that CGM may be a more practical, patient-centered tool in ESRD patients with diabetes [73 ▪ ]. Although clinical practice guidelines support the use of daily glycemic monitoring with CGM in CKD patients with diabetes [52], particularly in the context of use of glucose-lowering pharmacotherapies with hypoglycemia risk, such as insulin and insulin secretagogues (sulfonylureas, glinides), this convenient tool remains under-utilized in the kidney disease population.…”
Section: Management Of Hypoglycemia and Glycemic Derangements In Chro...mentioning
confidence: 87%
See 2 more Smart Citations
“…In non-CKD patients, clinical trials have shown that CGM is superior to SMBG in hypoglycemia detection and improved clinical outcomes. Several studies support the agreement of blood versus CGM-based interstitial glucose levels in advanced CKD patients [74–76], and anecdotal reports suggest that CGM may be a more practical, patient-centered tool in ESRD patients with diabetes [73 ▪ ]. Although clinical practice guidelines support the use of daily glycemic monitoring with CGM in CKD patients with diabetes [52], particularly in the context of use of glucose-lowering pharmacotherapies with hypoglycemia risk, such as insulin and insulin secretagogues (sulfonylureas, glinides), this convenient tool remains under-utilized in the kidney disease population.…”
Section: Management Of Hypoglycemia and Glycemic Derangements In Chro...mentioning
confidence: 87%
“…>10 times/day) has been shown to result in better glycemic control, such that the ADA advises at least 6–10 daily SMBG measurements in patients with diabetes receiving intensive insulin regimens [72], frequent capillary fingerstick measurements may be inconvenient, burdensome, and painful for patients. Furthermore, the above-mentioned glycemic metrics do not adequately capture daily glucose dynamics, including asymptomatic, nocturnal, nor intra-dialytic hypoglycemia and hyperglycemia events [11 ▪ ,73 ▪ ].…”
Section: Management Of Hypoglycemia and Glycemic Derangements In Chro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the potential advantages of the long-term use of personal CGM, published data are extremely limited. A recently published case report illustrated the utility of transitioning from SBMG to CGM in terms of decreasing patient burden, improving glucose monitoring adherence, improving glucose metrics (especially less glycemic variability and increased TIR) and reducing hypoglycemia occurrence after 2 years of follow-up [45]. The patient included in this case report was relatively young (49 years) and very motivated to use CGM for the long term.…”
Section: What Is the Role Of Cgm In Improving Diabetes Management In ...mentioning
confidence: 95%
“…Source: Reproduced from Narasaki et al 15 with permission from John Wiley & Sons—Books; permission conveyed through Copyright Clearance Center, Inc.…”
Section: Session 5 Special Situations: Labor/delivery and Hemodialysismentioning
confidence: 99%